Sin sick : moral injury in war and literature - Pederson, Joshua (Cornell University Press, 2021)
"Moral injury is the name given to the lasting psychological damage that sometimes follows the commission or witnessing of a grievous wrong. This book introduces the concept to literary trauma studies while identifying and analyzing notable examples of moral injury in a variety of novels, poems, and plays"--